The New Normal of Working Lives Critical Studies in Contemporary Work and Employment (Dynamics of Virtual Work, 2018)
This critical, international and interdisciplinary edited collection investigates the new normal of work and employment, presenting research on the experience of the workers themselves. The collection explores the formation of contemporary worker subjects, and the privilege or disadvantage in play around gender, class, age and national location within the global workforce. Organised around the three areas of: creative working, digital working lives, and transitions and transformations, its fifteen chapters examine in detail the emerging norms of work and work activities in a range of occupations and locations. It also investigates the coping strategies adopted by workers to manage novel difficulties and life circumstances, and their understandings of the possibilities, trajectories, mobilities, identities and potential rewards of their work situations. This book will appeal to a wide range of audiences, including students and academics of the sociology of work and labor history, and those interested in understanding the implications of the 'new normal' of work and employment.